1999
DOI: 10.1029/1998tc900024
|View full text |Cite
|
Sign up to set email alerts
|

History and tectonic implications of low‐angle detachment faults and orogen parallel extension, Picentini Mountains, Southern Apennines fold and thrust belt, Italy

Abstract: Abstract. Late Miocene to Pliocene movement on low-angle extensional faults within the internal Southern Apennines orogenic belt was superposed on an earlier, Miocene imbricate thrust stack. The low-angle faults formed within the interior of the belt during orogen parallel extension as thrust imbrication continued in the foreland. Extreme tectonic thinning defines discrete structural domains of hyperextension which are linked by a complex system of extensional and transcurrent faults. Some of the best examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The Picentini detachment appears, in its western part (Monte Stella–Monte Monna zones), as a clearly inactive structure. This is demonstrated by stratigraphical and geomorphological considerations [ Ferranti and Oldow , 1999; Casciello et al , 2006] but also suggested by its subhorizontal attitude, its wave‐shaped trajectory and the crosscut relationships with the SAf high‐angle normal faults. The eastern part, gradually sloping under the Acerno–Monte Raimagra ridge, might acts instead, as a presently active fault on which the high‐angle normal faults, including the SAf and Irf detach.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The Picentini detachment appears, in its western part (Monte Stella–Monte Monna zones), as a clearly inactive structure. This is demonstrated by stratigraphical and geomorphological considerations [ Ferranti and Oldow , 1999; Casciello et al , 2006] but also suggested by its subhorizontal attitude, its wave‐shaped trajectory and the crosscut relationships with the SAf high‐angle normal faults. The eastern part, gradually sloping under the Acerno–Monte Raimagra ridge, might acts instead, as a presently active fault on which the high‐angle normal faults, including the SAf and Irf detach.…”
Section: Discussionmentioning
confidence: 81%
“…In the internal side of the Campania‐Lucania arc, extension generated both low‐angle (LANFs) and high‐angle normal faults. LANFs have been recognized as the cause of diffuse younger‐on‐older subhorizontal tectonic contacts in the Picentini, Maddalena, Lauria and Morano Calabro Mountains [ D ' Argenio et al , 1987; D ' Argenio and Ietto , 1988; Ietto et al , 1992; Ferranti et al , 1996; Ferranti and Oldow , 1999; Casciello et al , 2004, 2006] and have been generally referred to an early extensional stage preceding the origin of the high‐angle normal faults bounding the Quaternary basins.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1992b; Wallis et al. , 1993; Wells, 1997; Ferranti & Oldow, 1999; Collins, 2002). Despite the theoretical predictions and field examples of alternating shortening and extension, P – T paths confirming such alternations are not widely reported (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…England & Thompson, 1984). In parallel with the recognition that plate boundary forces, gravitational potential energy, rock rheology and erosion dynamically interact to influence deformation kinematics (Davis et al, 1983;Platt, 1986;Molnar & Lyon-Caen, 1988;England & Houseman, 1989;Royden, 1993;Rey et al, 2001), orogenic histories involving synconvergent extension and alternations in shortening and extension have been documented (Hodges et al, 1992b;Wallis et al, 1993;Wells, 1997;Ferranti & Oldow, 1999;Collins, 2002). Despite the theoretical predictions and field examples of alternating shortening and extension, P-T paths confirming such alternations are not widely reported (e.g.…”
Section: Introductionmentioning
confidence: 99%